Кiнетична модель просторового розподiлу електронних збуджень в рiдинних люмiнофорах - Degoda, V. Ya.; Moroz, I. M. (Publishing house "Academperiodika", 2019)
A model of luminescence in liquid phosphors under X-ray excitation has been proposed. The corresponding spatial distributions for electronic excitations and local heating are obtained. They are described by Gaussian functions, the parameters of which are related to the kinetic energy of an X-ray quantum and the medium characteristics. The explanation to a low quantum yield of luminescence in liquid phosphors under the X-ray excitation in comparison with a high quantum yield at the photoluminescence is given. It is shown that the major losses in this case occur at the stage of electronic excitation migration from the solvent to phosphor molecules.